Elastic aftereffect in the process of asphalt concrete mixture compaction - Shishkin E.A.; Ivanchenko S.N.; Smolyakov A.A. (Научно-технический вестник Брянского государственного университета)
Asphalt concrete of various brands is mainly used as a road surface. The quality and durability of the coating depends on its density. To achieve the required density of the asphalt concrete pavement, road rollers are used. The working body of the roller is a metal drum or a set of pneumatic tires. The article discusses the process of the asphalt concrete mixture compaction with a smooth metal drum. A rheological model of the force interaction of a smooth drum with a material is adopted, which includes elastic, viscous and plastic elements. The adopted model was corrected taking into account the investigated process of elastic aftereffect that occurs in the asphalt concrete mixture during compaction. The law of behavior of asphalt-concrete mixture with elastic aftereffect is established. A simulation model has been developed to study the behavior of a material in the process of elastic aftereffect. In the course of dynamic modeling, the relationship between the physical and mechanical characteristics of the compacted material with the design and technological parameters of the road roller was established. A statistical analysis of the design parameters of existing models of road rollers has been carried out. The results of the analysis, as well as the obtained dependencies, can be used to designate the technological modes of operation of a set of road rollers when compacting the asphalt concrete pavement of a motor road. Taking into account the elastic aftereffect when assigning the operating modes of the compaction equipment will improve the compaction efficiency, as well as the quality of the resulting coating.